2019
DOI: 10.3390/cells8050411
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of YAP/TAZ and the Hippo Pathway in Healthy and Diseased Skin

Abstract: Skin is the largest organ of the human body. Its architecture and physiological functions depend on diverse populations of epidermal cells and dermal fibroblasts. Reciprocal communication between the epidermis and dermis plays a key role in skin development, homeostasis and repair. While several stem cell populations have been identified in the epidermis with distinct locations and functions, there is additional heterogeneity within the mesenchymal cells of the dermis. Here, we discuss the current knowledge of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 217 publications
(464 reference statements)
2
83
0
Order By: Relevance
“…The findings of this study are especially relevant to children with congenital heart disease or pulmonary hypertension who are chronically exposed to either left or right ventricular pressure overload and whose outcomes are dependent upon the maintenance of ventricular function. Importantly, children with pressure overload of the right ventricle have no effective medical treatment beyond heart transplantation (1, 6), and thus targeting SLIT3 or fibroblast-specific YAP1 activation (59,98,99), rather than cardiomyocyte-specific YAP1 activation (100), may a promising strategy to inhibit adverse remodeling and preserve ventricular function by reducing fibrosis (101). Furthermore, MI is rare in children, and hence myocardial rupture after infarction as a potential side effect of SLIT3 inhibition would be unusual in children with ventricular pressure overload.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study are especially relevant to children with congenital heart disease or pulmonary hypertension who are chronically exposed to either left or right ventricular pressure overload and whose outcomes are dependent upon the maintenance of ventricular function. Importantly, children with pressure overload of the right ventricle have no effective medical treatment beyond heart transplantation (1, 6), and thus targeting SLIT3 or fibroblast-specific YAP1 activation (59,98,99), rather than cardiomyocyte-specific YAP1 activation (100), may a promising strategy to inhibit adverse remodeling and preserve ventricular function by reducing fibrosis (101). Furthermore, MI is rare in children, and hence myocardial rupture after infarction as a potential side effect of SLIT3 inhibition would be unusual in children with ventricular pressure overload.…”
Section: Discussionmentioning
confidence: 99%
“…YAP also plays an important role in maintaining normal skin homeostasis in response to extracellular cues by promoting cell proliferation in epidermal stem and progenitor cells, and tissue expansion [80,81] Genetic analysis showed that YAP is highly expressed and shows nuclear localization in epidermal progenitor and stem cells, revealing a requirement for TEAD to mediate YAP’s functions in controlling their self-renewal and maintaining their undifferentiated state [82]. Moreover, enhanced nuclear YAP/TAZ levels have been detected in the dermis during the skin wound-healing process.…”
Section: The Hippo Pathway In Organ Fibrosismentioning
confidence: 99%
“…Hippo pathway is a well-conserved signaling pathway, which is important in skin development, cutaneous homeostasis and tissue regeneration, and aberrant Hippo signaling has been noted in non-melanoma skin cancers [125]. Recently, upregulation of a previously unknown lncRNA, LINC01048, was reported in cSCC associated with lower overall survival of cSCC patients [126].…”
Section: Linc01048 and Hippo Pathway In Keratinocyte Carcinomamentioning
confidence: 99%